YAG / Yb: YAG / YAG composite laser transparent ceramic and preparation method thereof
By using Yb:YAG water-based ceramic ink combined with dry pressure and inkjet printing technology, the problem of difficulty in preparing YAG/Yb:YAG/YAG composite laser transparent ceramics with complex shapes and thin-layer structures in the prior art is solved, and high-precision and low-cost preparation is achieved, with good optical quality and high density.
Patent Information
- Application Number
- CN202311193071.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-15
AI Technical Summary
It is difficult to effectively prepare YAG/Yb:YAG/YAG composite laser transparent ceramics with complex shapes and thin-layer structures. The common molding methods are complex, time-consuming, and are prone to holes and surface defects.
YAG/Yb:YAG/YAG composite laser transparent ceramics are prepared by a molding method combining dry pressure and inkjet printing. The ink consists of Al2O3, Y2O3, Yb2O3 powder, dispersant, pH control agent, moisturizer, binder and sintering additive. It is prepared by ball milling and ultrasonic dispersion to ensure the high dispersion and stability of the ink.
It has achieved high precision and low cost preparation of YAG/Yb:YAG/YAG composite laser transparent ceramics with complex shapes and thin-layer structures. It has good optical quality and high density, and the process is stable and adjustable, suitable for mass production and a variety of application scenarios.
Smart Images

Figure CN119638400A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite multilayer laser transparent ceramic preparation, and specifically relates to a YAG / Yb:YAG / YAG composite laser transparent ceramic and a preparation method thereof. Background Art
[0002] Yttrium aluminum garnet (YAG) is Al 2 O 3 and Y 2 O 3 A cubic isotropic crystal is formed by mixing in a molar ratio of 5:3 and undergoing a high-temperature solid solution reaction. YAG crystal is a solid laser matrix material with good optical, thermal, mechanical and mechanical properties. It is doped with rare earth or other transition metal ions with similar radii to partially replace the Y in the YAG lattice. 3+ By adjusting the position of the ions, the metal ion energy level of YAG can be increased to achieve laser output of multiple wavelengths.
[0003] Since the advent of solid-state lasers in the 1960s, solid-state laser gain media have mainly used single crystals and glass materials, among which Nd:YAG single crystals are more typical. In 1984, the Dutchman De proposed the idea of replacing single crystals with polycrystalline ceramics and successfully prepared YAG transparent ceramics. In 1995, Ikesu et al. in Japan prepared YAG and Nd:YAG transparent ceramics with comprehensive properties such as light absorption and fluorescence, hardness, and thermal conductivity comparable to single crystals for the first time through high-purity powder solid-phase reaction and vacuum sintering, showing the good application prospects of polycrystalline YAG ceramics in solid-state lasers. Compared with single crystals, transparent ceramics have the following advantages: low production cost; simple production process and short cycle; easy to prepare large-size samples to increase laser output power; easy to achieve high-concentration rare earth ion doping to increase laser output power.
[0004] At present, YAG transparent ceramics are mainly formed by powder dry pressing, which has a simple process and high density after sintering. However, the poor flow of powder during dry pressing may lead to uneven density distribution of the green body, and the shape of the formed body is limited by the mold, which is often relatively simple. The subsequent processing of ceramic green bodies with more complex shapes is also more time-consuming and labor-intensive. Wet molding has the advantages of good slurry fluidity, adjustable solid content, and easy preparation of green bodies with uniform density, but the shape and size of the formed body are still limited by the mold.
[0005] For multi-layer or planar waveguide composite ceramic configurations with thin-layer structures, dry pressing is obviously difficult to achieve. Currently, the most common molding methods are tape casting and bonding. Tape casting is a process in which an organic solvent such as ethanol is used as a ceramic dispersion medium, and organic additives such as dispersants, sintering aids, binders, plasticizers, and lubricants are added to grind the slurry into a slurry. The slurry is applied to a special base tape with a certain thickness by scraping and pressing with a scraper. After drying and curing, the film of the green tape is peeled off from the top, and then the green tape is punched, laminated, and processed according to the size and shape of the finished product to make a finished blank to be sintered. This method has better thickness uniformity control, but the preparation process is complicated and time-consuming. In addition, the use of organic matter as a ceramic dispersion medium will significantly increase the difficulty and speed of debonding. There may be more holes after debonding, which are not easy to completely eliminate through subsequent heat treatment. Bonding is a method of attracting two sintered heterogeneous materials together through van der Waals forces or even atomic forces to form a composite structure. This method has very high requirements on the surface cleanliness and roughness of the bonding surface of the materials. The roughness is often even below the nanometer level, which makes the processing difficult, and there is a certain chance of failure after room temperature bonding or hot bonding.
[0006] 3D printing technology can realize the molding of complex structures and components with high precision while maintaining the advantages of wet molding. For thin layer structures of hundreds or even tens of microns, direct ink writing (DIW) is limited by high solid content and high viscosity slurry, so it is difficult to print lines of sub-thickness. A more suitable printing method is inkjet printing (IJP), which uses ink-like slurry with lower solid content to improve the fluidity of the ink after printing, has higher printing accuracy and speed, and simple process. Considering that the organic content in water-based slurry is low, debonding is easier, and there are fewer defects such as voids after debonding, and the density of the blank is higher, water-based ceramic ink is a better choice. Summary of the invention
[0007] In view of the above technical problems, the object of the present invention is to provide a Yb:YAG water-based ceramic ink (slurry) with good rheological properties and a preparation method thereof, as well as a YAG / Yb:YAG / YAG multilayer composite laser transparent ceramic prepared by a molding method combining dry pressing and inkjet printing.
[0008] In a first aspect, the present invention provides a Yb:YAG water-based ceramic ink, wherein the Yb:YAG water-based ceramic ink comprises: Al 2 O 3 Powder, Y 2 O 3 Powder, Yb 2 O 3 The solid content of the mixed powder is 20-25 vol%, and the Al 2 O 3 Powder, Y2 O 3 Powder and Yb 2 O 3 The molar ratio of the powder is 5:3-x:x, 0 <x≤0.3; Dispersant; the content of the dispersant is 0.2-0.8wt% of the mass of the mixed powder; pH control agent; the amount of the pH control agent is controlled to adjust the pH of the Yb:YAG water-based ceramic ink to between 10-11.5 and the pH of the ink is ≥9.5 within 24 hours under the conditions of sealing and 20-25°C; Moisturizing agent; the content of the moisturizing agent is 5-20 vol% of the total volume of the Yb:YAG water-based ceramic ink; Binder; the content of the binder is 0.1-0.5wt% of the mass of the mixed powder; Sintering aid; the content of the sintering aid is 0.1-0.5wt% of the mass of the mixed powder.
[0009] Preferably, the dispersant is selected from at least one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, and PVP; The pH control agent is selected from at least one of ammonia water, triethanolamine, tetraethylenepentamine, and N-(2-hydroxyethyl)ethylenediamine; The moisturizing agent is selected from at least one of diethylene glycol, glycerin, and propylene glycol methyl ether; The binder is selected from at least one of PVA, PVB, PEG and Isobam; The sintering aid is selected from MgO, MgAl 2 O 4 ,La 2 O 3 , Gd 2 O 3 Sc 2 O 3 、TiO 2 、MnO 2 、SiO 2 、CaO、CuO、MgCO 3 、CaCO 3 、SrCO 3 、BaCO 3 , TEOS.
[0010] In a second aspect, the present invention provides a method for preparing the above Yb:YAG water-based ceramic ink, comprising the following steps: 2 O 3 Raw material powder, Y 2 O 3 Raw material powder and Yb2 O 3 The raw material powder is added with ethanol, and then subjected to the first ball milling mixing, the first filtration, drying and sieving to obtain the Yb:YAG raw material powder; then, the Yb:YAG raw material powder is added with water, and then mixed with a dispersant, a pH control agent, a moisturizing agent and a sintering aid by the second ball milling, the second filtration, and then a binder is added and ultrasonic dispersion is performed; and the Yb:YAG water-based ceramic ink is obtained by centrifugal mixing, centrifugal degassing and degassing.
[0011] Preferably, Al 2 O 3 The purity of raw material powder is ≥99.9%, and the particle size is 0.1-1μm; 2 O 3 The purity of raw material powder is ≥99.9%, and the particle size is 0.5-10μm; Yb 2 O 3 The purity of the raw material powder is ≥99.9% and the particle size is 0.5-10μm.
[0012] Preferably, the first ball milling and the second ball milling use Al2O3 with a particle size of 3 mm and / or 5 mm. 2 O 3 grinding balls; The ethanol used in the first ball milling was chemically pure and the amount of Al 2 O 3 Powder, Y 2 O 3 Powder and Yb 2 O 3 0.8-1.5 times of the total mass of the powder, the ball milling mixing time is 18-48h, the ball milling speed is 80-200r / min; the first filtration uses a funnel-shaped screen with a mesh size of 40-60 meshes; the drying temperature is 50-120°C, and the drying time is 12-36h; the mesh size of the sieving screen is 60-120 meshes, and the number of sieving times is 1-3 times; The water used for the second ball milling is deionized water, and the amount added is calculated according to the solid content requirement of the ink; the Yb:YAG raw material powder and Al 2 O 3 The mass ratio of the grinding balls is 1:1.6-2.5; the ball milling time is 18-32h, and the ball milling speed is 100-200r / min; the second filtration uses a funnel-shaped screen with a mesh size of 40-60; The frequency of the ultrasonic dispersion is 50-53 kHz, and the ultrasonic time is 5-10 min.
[0013] Preferably, the rotation speed of the centrifugal mixing is 1000-2000 r / min, and the centrifugal time is 3-6 min; the rotation speed of the centrifugal degassing is 1000-2000 r / min, the time is 5-10 min, and the vacuum degree is 1-10 kPa.
[0014] In a third aspect, the present invention provides a method for preparing a YAG / Yb:YAG / YAG composite laser transparent ceramic, comprising the following steps: 2 O 3 Raw material powder, Y 2 O 3 The raw material powders are mixed to obtain YAG raw material powder; then, the YAG raw material powder is dry-pressed to form a YAG first-layer blank, and then the Yb:YAG water-based ceramic ink is 3D inkjet-printed on the YAG first-layer blank to form a Yb:YAG layer blank, and then the YAG raw material powder is dry-pressed on the Yb:YAG layer blank to form a YAG second-layer blank to obtain a YAG / Yb:YAG / YAG composite laser transparent ceramic blank; after cold isostatic pressing, debinding, sintering, hot isostatic pressing and annealing, the YAG / Yb:YAG / YAG composite laser transparent ceramic is obtained.
[0015] Preferably, the mixing method of the YAG raw material powder is the same as the mixing method of the above-mentioned Yb:YAG raw material powder.
[0016] Preferably, the process parameters of the 3D inkjet printing include: surface air path pressure of 0.2-5psi, voltage signal frequency of 20-100Hz, pulse time of 0.3-0.5ms, nozzle aperture of 50-100μm, printing linear speed of 8-20mm / s, and printing line spacing of 0.2-0.5mm.
[0017] Preferably, the cold isostatic pressing pressure is 180-250 MPa, and the time is 0.5-2 h; The debonding environment is air, the temperature is 600-1000°C, and the time is 1-3h; The sintering is carried out under vacuum, and the pressure is controlled to be ≤10 -2 Pa, temperature is 1640-1750℃, time is 8-15h; The hot isostatic pressing atmosphere is argon, the pressure is 160-250 MPa, the temperature is 1600-1700°C, and the time is 3-6 hours; The annealing atmosphere is air or oxygen, the temperature is 1250-1350° C., and the time is 10-20 hours.
[0018] In a fourth aspect, the present invention provides a YAG / Yb:YAG / YAG composite laser transparent ceramic obtained according to the above preparation method, wherein the YAG / Yb:YAG / YAG composite laser transparent ceramic has a cubic phase isotropic structure of YAG and Yb:YAG components, an average grain size of 2-10 μm, a relative density of ≥99.9%, and a thickness of the Yb:YAG layer of 50-250 μm; When the thickness of the YAG / Yb:YAG / YAG composite laser transparent ceramic sample is 4.5-5.5 mm, the linear transmittance at a wavelength of 1030 nm is ≥80%.
[0019] Beneficial Effects (1) The Yb:YAG water-based ceramic ink of the present invention has high dispersibility and stability, and does not settle or stratify within a specific period of time; (2) The Yb:YAG water-based ceramic ink of the present invention has the characteristics of low solid content and low viscosity, and is particularly suitable for 3D printing of ceramic samples with thin layers and flexible shapes and sizes by inkjet printing; (3) The Yb:YAG water-based ceramic ink of the present invention can be used to prepare YAG / Yb:YAG / YAG composite transparent ceramics with good optical quality through inkjet printing and dry pressing and subsequent densification and heat treatment processes, which proves the practicality of the ceramic ink; (4) The Yb:YAG water-based ceramic ink of the present invention does not contain toxic heavy metal ions, and the organic matter contained is low in toxicity and content, and can be completely decomposed into harmless gas during the heat treatment process, and is a healthy and environmentally friendly preparation material; (5) The raw materials used in the present invention are of stable source, and the molding and densification processes are stable and adjustable. The process can be fixed to implement mass production, or the process parameters can be fine-tuned to meet the needs of various application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the YAG / Yb:YAG / YAG composite laser transparent ceramic prepared in Example 1 and its transmittance curve; Figure 2 The viscosity of the Yb:YAG water-based ceramic ink used in Example 1 and Comparative Examples 1 and 2 varies with shear rate; Figure 3 The inkjet printing effect diagram of using the ink in Example 1 (right side) and the ink in Comparative Example 2 (left side) on the dry pressed YAG blank; Figure 4 Schematic diagram of the sedimentation effect of the Yb:YAG water-based ceramic ink used in Examples 1 and 2 and Comparative Examples 3 and 4 after being left in a sealed sample bottle for one week; Figure 5Schematic diagram of the composite ceramic samples after hot isostatic pressing treatment of Example 2 (left figure) and Comparative Example 5 (right figure). DETAILED DESCRIPTION
[0021] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.
[0022] The following is an exemplary description of the preparation method of the YAG / Yb:YAG (ytterbium-doped yttrium aluminum garnet) / YAG composite laser transparent ceramic provided by the present invention. The preparation method of the YAG / Yb:YAG / YAG composite laser transparent ceramic may include the following steps.
[0023] (1) Preparation of YAG raw material powder. 2 O 3 Raw material powder, Y 2 O 3 Raw material powder, ethanol, high purity Al 2 O 3 The grinding balls are mixed by ball milling in a ball mill jar, and the YAG raw material powder is obtained through filtering, drying and sieving.
[0024] In some embodiments, the Al 2 O 3 The purity of the raw material powder is ≥99.9%, and the particle size is 0.1-1μm; 2 O 3 The purity of the raw material powder is ≥99.9% and the particle size is 0.5-10 μm. 2 O 3 Raw material powder, Y 2 O 3 The molar ratio of the raw material powder is 5:3.
[0025] In some embodiments, the purity of the ethanol can be chemically pure, and the amount added can be controlled to be Al 2 O 3 Raw material powder, Y 2 O 3 0.8-1.5 times the total mass of raw material powder.
[0026] In some embodiments, the high purity Al 2 O 3 The particle size of the grinding balls can be 3 mm or / and 5 mm; Al 2 O 3 Raw material powder, Y 2 O 3 Total mass of raw material powder and high purity Al 2 O 3The mass ratio of the grinding balls can be controlled to be 1:1.6 - 2.5; the volume of the ball mill tank can be 1 - 5 L, the ball milling speed can be 80 - 200 r / min, and the ball milling time can be 18 - 48 h; preferably, the volume of the grinding tank is 5 L, the ball milling speed is 100 r / min, and the ball milling time is 48 h.
[0027] In some embodiments, the filtration can be carried out using a funnel-shaped screen, and the mesh number can be 40 - 60 meshes.
[0028] In some embodiments, the drying temperature can be 50 - 120 °C, and the drying time can be 12 - 36 h; preferably, the drying temperature is 80 °C and the drying time is 18 h.
[0029] In some embodiments, the mesh number of the screen for the screening process can be 60 - 120 meshes, and the number of screening times can be 1 - 3 times; preferably, the mesh number of the screen is 100 meshes and the number of screening times is 2 times.
[0030] (2) Preparation of Yb:YAG raw material powder. Al 2 O 3 raw material powder, Y 2 O 3 raw material powder, and Yb 2 O 3 raw material powder are mixed with ethanol and high-purity Al 2 O 3 grinding balls in a ball mill tank for the first ball milling and mixing, and after filtration, drying, and screening treatments, the Yb:YAG raw material powder is obtained.
[0031] In some embodiments, the purity of the Al 2 O 3 raw material powder is ≥99.9%, and the particle size is 0.1 - 1 μm; the purity of the Y 2 O 3 raw material powder is ≥99.9%, and the particle size is 0.5 - 10 μm; the purity of the Yb 2 O 3 raw material powder is ≥99.9%, and the particle size is 0.5 - 10 μm. Preferably, the molar ratio of the Al 2 O 3 raw material powder, Y 2 O 3 raw material powder, and Yb 2 O 3 raw material powder can be 5:3 - x:x, where 0 < x ≤ 0.3. If the value of x is too large, it will lead to too high a Yb concentration, which is likely to cause concentration quenching and reduce the luminescence efficiency of the Yb:YAG ceramic.
[0032] In some embodiments, the purity of the ethanol can be chemically pure, and the added amount can be controlled as Al2 O 3 Raw material powder, Y 2 O 3 Raw material powder and Yb 2 O 3 0.8-1.5 times the total mass of raw material powder.
[0033] In some embodiments, the high purity Al 2 O 3 The particle size of the grinding balls can be 3 mm and / or 5 mm; 2 O 3 Raw material powder, Y 2 O 3 Raw material powder and Yb 2 O 3 Total mass of raw material powder and high purity Al 2 O 3 The mass ratio of the grinding balls can be 1:1.6-2.5; the volume of the ball mill can be 1-5L, the ball mill speed can be 80-200r / min, and the ball milling time can be 18-48h; preferably, the volume of the grinding jar is 5L, the ball mill speed is 100r / min, and the ball milling time is 48h.
[0034] In some embodiments, the filtration may be performed using a funnel-shaped screen with a mesh size of 40-60.
[0035] In some embodiments, the drying temperature may be 50-120° C., and the drying time may be 12-36 hours; preferably, the drying temperature is 80° C., and the drying time is 18 hours.
[0036] In some embodiments, the mesh size of the sieve for the sieving process may be 60-120 meshes, and the number of sieving may be 1-3 times; preferably, the mesh size of the sieve is 100 meshes, and the number of sieving is 2 times.
[0037] (3) Preparation of Yb:YAG water-based ceramic ink. The Yb:YAG raw material powder is added to deionized water and mixed with a dispersant, a pH control agent, a moisturizer, a sintering aid, and a high-purity Al 2 O 3 The grinding balls are placed in a ball mill for a second ball milling to mix and disperse evenly, then the mixed solution after ball milling is filtered into a degassing tank and a binder is added to the filtrate for ultrasonic dispersion, and finally the degassing tank containing the mixed solution is placed in a centrifuge for centrifugal mixing, centrifugal degassing, and filtering to obtain the Yb:YAG water-based ceramic ink.
[0038] Among them, the sintering aid can be added before ball milling, but the binder cannot, because the ball milling time is long, and the long-term mixing of the binder and other slurries will greatly increase the viscosity of the slurry, thereby reducing the dispersion effect and printability of the ink.
[0039] In some embodiments, the dispersant may be selected from at least one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, and PVP; the pH control agent may be selected from at least one of ammonia water, triethanolamine, tetraethylene pentamine, and N-(2-hydroxyethyl)ethylenediamine; the humectant may be selected from at least one of diethylene glycol, glycerol, and propylene glycol methyl ether; the binder may be selected from at least one of PVA, PVB, PEG, and Isobam; the sintering aid may be selected from MgO, MgAl 2 O 4 ,La 2 O 3 , Gd 2 O 3 Sc 2 O 3 、TiO 2 、MnO 2 、SiO 2 、CaO、CuO、MgCO 3 、CaCO 3 、SrCO 3 、BaCO 3 , TEOS.
[0040] In some embodiments, the purity of the dispersant, pH control agent, and binder may be chemically pure; the purity of the humectant and sintering aid may be analytically pure.
[0041] In some embodiments, the Yb:YAG raw material powder and high purity Al 2 O 3 The mass ratio of the grinding balls can be 1:1.6-2.5; preferably, the high purity Al 2 O 3 The particle size of the grinding balls can be 3 mm and / or 5 mm.
[0042] In some embodiments, the volume of the ball milling tank can be 500 ml, the ball milling time can be 18-32 hours, and the rotation speed can be 100-200 r / min; preferably, the ball milling time is 24 hours and the rotation speed is 120 r / min. If the ball milling time is too short, the powder in the slurry is not fully dispersed, and some particles are agglomerated; if the ball milling time is too long, the water in the slurry is easy to evaporate slowly from the micro-slits of the tank mouth, thereby increasing the solid content and viscosity of the slurry, affecting the effect of inkjet printing.
[0043] In some embodiments, the filtration may be performed using a funnel-shaped screen with a mesh size of 40-60.
[0044] In some embodiments, the ultrasonic dispersion may have an ultrasonic frequency of 50-53 kHz and an ultrasonic time of 5-10 min.
[0045] In some embodiments, the centrifugal mixing speed may be 1000-2000 r / min, and the centrifugal time may be 3-6 min; preferably, the centrifugal speed is 1500 r / min, and the centrifugal time is 5 min.
[0046] In some embodiments, the speed of the centrifugal degassing can be 1000-2000 r / min, the time can be 5-10 min, and the vacuum degree can be 1-10 kPa; preferably, the centrifugal speed is 1500 r / min, the time is 6 min, and the vacuum degree is 1 kPa.
[0047] In some embodiments, in the Yb:YAG water-based ceramic ink, Al 2 O 3 Powder, Y 2 O 3 Powder, Yb 2 O 3 The solid content of the mixed powder composed of the powder can be controlled to be 20-25 vol%; the content of the dispersant can be controlled to be 0.2-0.8 wt% of the mass of the mixed powder; the content of the pH control agent can be controlled to adjust the pH of the Yb:YAG water-based ceramic ink to between 10-11.5 and the ink pH is ≥9.5 within 24 hours under sealed conditions at 20-25°C; the content of the humectant can be controlled to be 5-20 vol% of the total volume of the Yb:YAG water-based ceramic ink; the content of the binder can be 0.1-0.5 wt% of the total mass of the mixed powder; the content of the sintering aid can be 0.1-0.5 wt% of the mass of the mixed powder.
[0048] In some embodiments, the viscosity of the Yb:YAG water-based ceramic ink can be controlled to be 1-100 mPa·s, preferably 1-20 mPa·s, and more preferably 3-10 mPa·s at a shear rate of more than 100 / s. If the viscosity is too low, the fluidity of the ink printed on the substrate will be too strong, which will reduce the precision of the printed edge; if the viscosity of the ink is too high, it will cause the ink to be difficult to eject, the fluidity of the ink printed on the substrate will be too weak, the uniformity of the blank after drying will decrease, and the printed blank will be prone to cracking or warping.
[0049] In some embodiments, the Yb:YAG water-based ceramic ink can be controlled to not delaminate within 48 hours. The rheological properties of the ink are good and can meet the time required for the composite ceramic dry pressing and inkjet printing process.
[0050] If the solid content of the Yb:YAG water-based ceramic ink is too low, the ink in the subsequent 3D inkjet printing nozzle will not be controlled by the piezoelectric signal and will flow out of the nozzle, and the ink printed on the substrate will have too strong fluidity and reduce the dimensional accuracy of the edge; if the solid content of the Yb:YAG water-based ceramic ink is too high, the ink will still be difficult to spray through the 3D inkjet printing nozzle under a higher air pressure or the nozzle will be easily clogged during the spraying process, and the ink printed on the substrate will have too weak fluidity and reduce the uniformity of the blank after drying.
[0051] If the dispersant content is too low, the powder will not be fully dispersed and some powder particles will agglomerate; if the dispersant content is too high, the powder dispersion effect has been saturated, and the increase in organic matter content will affect the subsequent debonding effect. In addition, since the dispersant basically achieves particle dispersion through the effects of steric hindrance and electrostatic repulsion, it is necessary to achieve a better dispersion effect in a certain pH environment. By adding an appropriate amount of pH control agent, the solvent pH can be controlled to a region with a larger absolute value of the zeta potential, thereby improving the dispersion effect of the dispersant. The addition of a humectant can slow down the ink viscosity at the nozzle during the printing waiting process, which is too high or even completely evaporated due to solvent evaporation, causing nozzle blockage, and slow down the evaporation rate of the wet blank water on the dry pressing substrate after printing to prevent cracking; adding too little will weaken the above effects, and adding too much will lead to excessive organic matter content, which will also affect the debonding effect. The binder is to appropriately increase the viscosity of the ink and thus improve the conformality of the ink after printing. Too little binder will result in high ink fluidity and low printing accuracy; too high a binder will cause the ink to be difficult to level on the substrate and the nozzle will be easily blocked. The addition of sintering aids can improve the sintering activity of oxide raw materials and reduce the sintering temperature. Too little content will lead to higher sintering temperature and higher energy consumption; too much content will lead to the introduction of more other metal ion impurities, affecting the optical quality.
[0052] The Yb:YAG water-based ceramic ink obtained by the preparation method provided by the present invention is 2 O 3 Powder, Y 2 O 3 Powder and Yb 2 O 3 Powder is the main raw material. By adding water, dispersant and pH regulator, ceramic particles in water can be dispersed and sedimentation can be reduced. A small amount of binder is added to adjust the viscosity of the ink. A humectant is added to reduce water evaporation and stabilize the viscosity and solid content of the ink. The solid content of the ink is determined by controlling the amount of liquids added such as water, pH control agent and humectant. Considering the hydration effect of oxide ceramic powder, an appropriate amount of water is added to completely compensate for the free water lost by the reaction with oxide ceramics and stabilize the solid content. A small amount of sintering aid is added to assist the sintering of ceramic powder to make it dense and transparent.
[0053] (4) Preparation of YAG / Yb:YAG / YAG composite laser transparent ceramics. The YAG raw material powder is formed into a YAG first-layer blank by dry pressing, and then Yb:YAG water-based ceramic ink is 3D inkjet printed on the YAG first-layer blank to form a Yb:YAG layer blank. Then, the YAG raw material powder is formed into a YAG second-layer blank by dry pressing on the Yb:YAG layer blank to obtain a YAG / Yb:YAG / YAG composite laser transparent ceramic blank; after cold isostatic pressing, debonding, sintering, hot isostatic pressing and annealing, the YAG / Yb:YAG / YAG composite laser transparent ceramic is obtained.
[0054] In some embodiments, the process of dry-pressing the YAG raw material powder into a YAG first-layer blank can be: loading the YAG powder into a metal mold with a cross-sectional size of 40×20 mm and shaking it to make it flat and compact, then pressurizing the closed mold with a uniaxial press to an actual pressure of 20-30 MPa, demolding, and obtaining the YAG first-layer blank.
[0055] In some embodiments, the process of 3D inkjet printing Yb:YAG water-based ceramic ink to form a Yb:YAG layer blank can be: the Yb:YAG water-based ceramic ink is loaded into a 3D inkjet printer syringe and connected to a surface gas path, and then the Yb:YAG water-based ceramic ink is printed on the YAG first layer blank through a piezoelectric ceramic controlled nozzle according to a set printing program, and dried to obtain a Yb:YAG layer blank.
[0056] Among them, the pressure of the surface air path can be 0.2-5psi; the voltage signal frequency of the piezoelectric ceramic control nozzle can be 20-100Hz, and the pulse time can be 0.3-0.5ms; the nozzle aperture can be 50-100μm, the printing line speed can be 8-20mm / s, and the printing line spacing can be 0.2-0.5mm.
[0057] The printing parameters can be adjusted according to the actual printing effect. For the formulated ink with stable rheological properties, the air pressure will affect the injection speed. If the air pressure is too low, it will be difficult for the nozzle of the injection valve to spray ink. If the air pressure is too high, the injection line will be too thick, the precision will be reduced, and it is easy to accumulate large droplets at the nozzle, causing the jet to change direction or even fork. The voltage signal frequency and opening time can control the opening time of the injection valve nozzle, thereby affecting the injection speed. A smaller nozzle aperture can promote thinner printing lines with higher precision, but a too small aperture may cause difficulty in ink spraying or even cause the nozzle to be clogged. The printing linear velocity is the translation rate of the nozzle. When the ink injection speed is constant, if the linear velocity is too small, the ink will accumulate too much on the unit length of the line, increasing the thickness of the printing layer. If the linear velocity is too large, it will easily lead to uneven or even discontinuous line width. The printing line spacing is the distance between the center axes of two adjacent printed lines. When the ink rheological properties, injection speed and printing line speed are certain, the printed line width is also certain. If the line spacing is too small, the two adjacent lines will partially overlap. Even if the ink can flow level, the thickness of the printed layer will increase. If it cannot flow level, the thickness of the overlapping area will increase, and the thickness of the printed layer will be uneven. If the line spacing is too large, the thickness of the adjacent area of the two adjacent lines will be reduced or even gaps will be created, which will also make the thickness of the printed layer uneven.
[0058] In some embodiments, the cold isostatic pressing pressure can be 180-220 MPa, the time can be 0.5-2 h; the debonding environment can be air, the temperature can be 600-1000 ° C, and the time can be 1-3 h; the sintering can be carried out under vacuum, and the pressure can be controlled to be ≤10 -2 Pa, the temperature can be 1640-1750°C, and the time can be 8-15h; the hot isostatic pressing atmosphere can be argon, the pressure can be 160-250MPa, the temperature can be 1600-1700°C, and the time can be 3-6h; the annealing atmosphere can be air or oxygen, the temperature can be 1250-1350°C, and the time can be 10-20h.
[0059] Cold isostatic pressing can improve the density of the green blank after dry pressing. Insufficient pressure and time will lead to insufficient density of the green blank, which is easy to crack after cold isostatic pressing or during sintering. Debonding can remove the residual organic matter in the composite ceramic green blank. Insufficient temperature and time will cause the organic matter in the green blank to be insufficiently decomposed or even not decomposed. Excessive temperature and time will cause the green blank to start powder remelting and grain growth before the organic matter decomposition process is completely completed, resulting in more defects in the sample. Sintering is the powder remelting and grain growth process of the sample after debonding. Insufficient temperature and time will cause the process to be incomplete, the sample has low crystallinity, and there are many defects such as pores; excessive temperature and time will cause the sample grains to grow too large, reducing the strength of the sample. Hot isostatic pressing is the process of outward migration and elimination of defects such as pores in the sample after sintering. Insufficient temperature, pressure and time will lead to incomplete elimination of defects. If the temperature, pressure and time exceed the reasonable range, in addition to not significantly improving the defect elimination effect, it will also affect the service life of the equipment and even cause damage. Annealing is the process of eliminating internal stress of the sample after hot isostatic pressing and oxidizing all Yb ions to +3 valence. Insufficient temperature and time will lead to incomplete annealing process, resulting in low strength and transmittance of the sample; excessive temperature and time will cause grain remelting and recrystallization in the sample, reducing the effect of sintering and hot isostatic pressing.
[0060] The phase formation of YAG is carried out through the solid phase reaction during the sintering process after forming. The process is as follows: Al 2 O 3 +2Y 2 O 3 →Y 4 Al 2 O 9 (YAM): (900-1100℃); Y 4 Al 2 O 9 +Al 2 O 3 →4YAlO 3 (YAP):(1100-1250℃); 3YAlO 3 +Al 2 O 3 →Y 3 Al 5 O 12 (YAG): (1400-1600°C). In the present invention, the raw material for forming the Yb:YAG structure is Al 2 O 3 , Y 2 O 3 and Yb 2 O 3 The phase formation of Yb:YAG is also carried out through the solid phase reaction during the sintering process after forming. The process is similar to that of YAG, except that Yb2 O 3 Replace part Y 2 O 3 and Al 2 O 3 Respond gradually.
[0061] In the YAG / Yb:YAG / YAG composite laser transparent ceramic obtained by the preparation method provided by the present invention, both the YAG and Yb:YAG components are of cubic phase isotropic structure, the average grain size is 2-10 μm, the relative density is ≥99.9%, and the thickness of the Yb:YAG layer is 50-250 μm. Among them, when the thickness of the YAG / Yb:YAG / YAG composite laser transparent ceramic sample is 4.5-5.5 mm, the linear transmittance at a wavelength of 1030 nm is ≥80%.
[0062] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0063] Example 1
[0064] The preparation method of the YAG / Yb:YAG / YAG composite laser transparent ceramic provided in this embodiment comprises the following steps: (1) Preparation of YAG raw material powder. Al and 2 O 3 Raw material powder (purity ≥ 99.9%, average particle size 0.24 μm) and Y 2 O 3 Raw material powder (purity ≥ 99.9%, average particle size 4.11 μm), then weigh twice the total mass of the two powders of high-purity Al 2 O 3 Grinding ball, measure ethanol equal to the total mass of the two powders, add them into a 5L ball mill, and ball mill for 48 hours at a speed of 100r / min; then filter with a funnel-shaped sieve, dry at 80°C for 18 hours, and sieve twice with a 100-mesh sieve to obtain the YAG raw material powder. (2) Preparation of Yb:YAG raw material powder. Al and YAG were weighed in a mass ratio of 254.90:321.79:29.55 (molar ratio of 5:2.85:0.15). 2 O 3(purity ≥ 99.9%, average particle size 0.24 μm), Y 2 O 3 (purity ≥ 99.9%, average particle size 4.11 μm) and Yb 2 O 3 The powder (purity ≥ 99.9%, average particle size 1 μm) is prepared by referring to the preparation process in step (1) to obtain the Yb:YAG raw material powder. (3) Preparation of Yb:YAG water-based ceramic ink. Weigh 30 g of Yb:YAG raw material powder and prepare it according to the solid content of 20 vol%. Use ammonia water and water to prepare a solution with pH = 11. Considering the hydration effect of oxide ceramic powder, weigh 29.3 ml of ammonia solution as solvent, weigh 0.1846 g of 65 wt.% CE-64 (ammonium polymethyl acrylate) aqueous solution as dispersant (CE-64 accounts for 0.4 wt.% of the mixed powder mass), 5.2 ml of diethylene glycol as humectant (20 vol% of the total volume of water-based ceramic ink), weigh 66 g of high-purity Al with a particle size of 5 mm. 2 O 3 The mixture was ball milled at a speed of 120 r / min in a 0.5L nylon jar for 24 h; then filtered into a degassing tank with a funnel-type screen, 0.03 g of polyethylene glycol 400 as a binder and 0.03 g of MgO as a sintering aid were weighed, added into the degassing tank and ultrasonicated at a frequency of 50 Hz for 5 min, then rotated in a centrifugal stirrer at a speed of 1500 r / min for 5 min to mix, and then rotated in a vacuum environment of 1 kPa at a speed of 1500 r / min for 6 min to degas, and filtered to obtain the Yb:YAG water-based ceramic ink. (4) Preparation of YAG / Yb:YAG / YAG composite laser transparent ceramics. Weigh 10g of YAG raw material powder and spread it flat in a 40×20mm rectangular mold. Pressurize it to an actual pressure of 20MPa. After dry pressing, the powder is inkjet printed with a layer of Yb:YAG water-based ceramic ink. The printing parameters are: surface air pressure of 0.8psi, voltage signal frequency of the piezoelectric ceramic control nozzle of 25Hz, pulse time of 0.4ms, nozzle aperture of 100μm, linear speed of 12mm / s, line spacing of 0.3mm, and then weigh 10g. The YAG raw material powder was spread on the printed blank and pressurized to an actual pressure of 30 MPa to obtain a YAG / Yb:YAG / YAG composite laser transparent ceramic blank. Then, the blank was vacuum sealed and cold isostatically pressed in hydraulic oil at a pressure of 200 MPa for 2 h to increase the density of the blank. Then, the blank was placed in an air atmosphere debinding furnace at a temperature of 800 ° C for 2 h to debond. The debonded blank was sintered in a vacuum environment at a pressure of 5×10 -3The YAG / Yb:YAG / YAG composite laser transparent ceramics are obtained by hot isostatic pressing in a hot isostatic pressing furnace in an argon environment at a pressure of 200 MPa, a temperature of 1650°C, and a time of 4 hours. The hot isostatically pressed samples are annealed in an annealing furnace in an oxygen environment at a temperature of 1290°C and a time of 15 hours. The samples are finally cut into the required size and double-sided polished to obtain the YAG / Yb:YAG / YAG composite laser transparent ceramics.
[0065] The YAG / Yb:YAG / YAG composite laser transparent ceramic prepared in Example 1 has a cubic phase isotropic structure, an average grain size of 3.14 μm, a relative density of 99.9%, a thickness of the Yb:YAG component of 70 μm, and a composite ceramic sample thickness of 5.5 mm. The linear transmittance at a wavelength of 1030 nm is 80.75% (see Figure 1 ).
[0066] Example 2
[0067] The preparation method of Example 2 is similar to that of Example 1, except that in step (2), Al 2 O 3 , Y 2 O 3 and Yb 2 O 3 The mass ratio of the powders was adjusted to 254.90:304.86:59.10 (molar ratio 5:2.7:0.3); in step (3), the ink ball milling dispersion time was 32 h.
[0068] The YAG / Yb:YAG / YAG composite laser transparent ceramic prepared by Example 2 has an isotropic cubic structure, an average grain size of 2.27 μm, a relative density of 99.9%, a thickness of the Yb:YAG layer of 200 μm, and a composite ceramic sample thickness of 4.5 mm. The linear transmittance at a wavelength of 1030 nm is 81.73%.
[0069] Comparative Example 1
[0070] The preparation method of this comparative example 1 refers to that of Example 1, with the main difference being that in step (3), the total amount of water and ammonia solution added is adjusted to 39.0 ml, the amount of diethylene glycol added is adjusted to 6 ml, and the solid content of the ink is controlled to be 10 vol%.
[0071] Comparative Example 2
[0072] The preparation method of this comparative example 2 refers to that of Example 1, with the main difference being that in step (3), the total amount of water and ammonia solution added is adjusted to 14.2 ml, the amount of diethylene glycol added is adjusted to 1.5 ml, and the solid content of the ink is controlled to 30 vol%.
[0073] Figure 2 The viscosity of the Yb:YAG water-based ceramic ink used in Example 1 and Comparative Examples 1 and 2 varies with shear rate. It can be seen from the figure that when the shear rate exceeds 100 / s, the viscosity of Example 1 and Comparative Example 2 is between 3-10 mPa·s, and the viscosity of Comparative Example 1 is relatively small, which will cause leakage when no piezoelectric signal is applied during the inkjet printing process.
[0074] Figure 3 The inkjet printing effect diagram of the ink prepared in Example 1 (right side) and the ink prepared in Comparative Example 2 (left side) on the dry pressed YAG blank is shown. It can be seen from the figure that the ink prepared in Example 1 is well formed on the YAG dry pressed blank, while the ink prepared in Comparative Example 2 quickly cracks on the YAG dry pressed blank.
[0075] Comparative Example 3
[0076] The preparation method of this comparative example 3 refers to that of Example 1, with the main difference being that in step (3), the ink ball milling dispersion time is 8 hours.
[0077] Comparative Example 4
[0078] The preparation method of this comparative example 4 refers to that of Example 1, with the main difference being that in step (3), the ink ball milling dispersion time is 16 hours.
[0079] Figure 4 The figure is a schematic diagram of the sedimentation effect of the Yb:YAG water-based ceramic ink used in Examples 1 and 2 and Comparative Examples 3 and 4 after being left in a sealed sample bottle for one week. It can be seen from the figure that the ink of Example 1 after ball milling for 24 hours and Example 2 after ball milling for 32 hours only showed a small supernatant stratification, and the ink was relatively stable, while the ink of Comparative Examples 3 and 4 showed obvious sedimentation and stratification.
[0080] Comparative Example 5
[0081] The preparation method of this comparative example 5 refers to that of Example 1, with the main difference being that in step (4), the printing linear speed is 25 mm / s and the printing line spacing is 0.5 mm.
[0082] Figure 5 Schematic diagram of the composite ceramic samples after hot isostatic pressing of Example 2 (left) and Comparative Example 5 (right). It can be seen from the figure that the printed layer of Example 2 is relatively uniform, while the thickness of the printed lines and line gaps of Comparative Example 5 is not uniform.
[0083] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A Yb:YAG water-based ceramic ink, characterized in that: The Yb:YAG water-based ceramic ink comprises: A mixed powder composed of Al2O3 powder, Y2O3 powder and Yb2O3 powder; the solid content of the mixed powder is 20-25vol%, and the molar ratio of the Al2O3 powder, Y2O3 powder and Yb2O3 powder is 5:3-x:x, 0 <x≤0.3; Dispersant; the content of the dispersant is 0.2-0.8wt% of the mass of the mixed powder; pH control agent; the amount of the pH control agent is controlled to adjust the pH of the Yb:YAG water-based ceramic ink to between 10-11.5 and the pH of the ink is ≥9.5 within 24 hours under the conditions of sealing and 20-25°C; Moisturizing agent; the content of the moisturizing agent is 5-20 vol% of the total volume of the Yb:YAG water-based ceramic ink; Binder; the content of the binder is 0.1-0.5wt% of the mass of the mixed powder; Sintering aid; the content of the sintering aid is 0.1-0.5wt% of the mass of the mixed powder.
2. The Yb:YAG water-based ceramic ink according to claim 1, characterized in that: The dispersant is selected from at least one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, and PVP; The pH control agent is selected from at least one of ammonia water, triethanolamine, tetraethylenepentamine, and N-(2-hydroxyethyl)ethylenediamine; The moisturizing agent is selected from at least one of diethylene glycol, glycerin, and propylene glycol methyl ether; The binder is selected from at least one of PVA, PVB, PEG and Isobam; The sintering aid is selected from at least one of MgO, MgAl2O4, La2O3, Gd2O3, Sc2O3, TiO2, MnO2, SiO2, CaO, CuO, MgCO3, CaCO3, SrCO3, BaCO3, and TEOS.
3. A method for preparing the Yb:YAG water-based ceramic ink according to claim 1 or 2, characterized in that: The following steps are involved: Al2O3 raw material powder, Y2O3 raw material powder and Yb2O3 raw material powder are added to ethanol, and then subjected to the first ball milling mixing, the first filtration, drying and sieving to obtain Yb:YAG raw material powder; then, the Yb:YAG raw material powder is added with water and mixed with a dispersant, a pH control agent, a moisturizing agent and a sintering aid by a second ball milling, the second filtration, and then a binder is added and ultrasonic dispersion is performed; and the Yb:YAG water-based ceramic ink is obtained by centrifugal mixing, centrifugal degassing and degassing.
4. The preparation method according to claim 3, characterized in that: The purity of Al2O3 raw material powder is ≥99.9%, and the particle size is 0.1-1μm; the purity of Y2O3 raw material powder is ≥99.9%, and the particle size is 0.5-10μm; the purity of Yb2O3 raw material powder is ≥99.9%, and the particle size is 0.5-10μm.
5. The preparation method according to claim 3 or 4, characterized in that: The first ball milling and the second ball milling use Al2O3 grinding balls with a particle size of 3 mm and / or 5 mm; The ethanol used for the first ball milling is chemically pure, and the amount added is 0.8-1.5 times the total mass of Al2O3 powder, Y2O3 powder and Yb2O3 powder. The ball milling mixing time is 18-48h, and the ball milling speed is 80-200r / min. The first filtration uses a funnel-shaped screen with a mesh size of 40-60 meshes; the drying temperature is 50-120°C, and the drying time is 12-36h; the mesh size of the sieving screen is 60-120 meshes, and the number of sieving times is 1-3 times; The water used for the second ball milling is deionized water, and the amount added is calculated according to the solid content requirement of the ink; the mass ratio of the Yb:YAG raw material powder and the Al2O3 grinding ball is 1:1.6-2.5; the ball milling time is 18-32h, and the ball milling speed is 100-200r / min; the second filtration uses a funnel-shaped screen with a mesh size of 40-60 mesh; The frequency of the ultrasonic dispersion is 50-53 kHz, and the ultrasonic time is 5-10 min.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The rotation speed of the centrifugal mixing is 1000-2000 r / min, and the centrifugal time is 3-6 min; the rotation speed of the centrifugal degassing is 1000-2000 r / min, the time is 5-10 min, and the vacuum degree is 1-10 kPa.
7. A method for preparing YAG / Yb:YAG / YAG composite laser transparent ceramics, characterized in that: The following steps are involved: Al2O3 raw material powder and Y2O3 raw material powder are mixed to obtain YAG raw material powder; then, the YAG raw material powder is dry-pressed to form a YAG first-layer blank, and then the Yb:YAG water-based ceramic ink is 3D inkjet-printed on the YAG first-layer blank to form a Yb:YAG layer blank, and then the YAG raw material powder is dry-pressed on the Yb:YAG layer blank to form a YAG second-layer blank to obtain a YAG / Yb:YAG / YAG composite laser transparent ceramic blank; after cold isostatic pressing, debonding, sintering, hot isostatic pressing and annealing, the YAG / Yb:YAG / YAG composite laser transparent ceramic is obtained.
8. The preparation method according to claim 7, characterized in that: The mixing method of the YAG raw material powder is the same as the mixing method of the Yb:YAG raw material powder described in claim 5.
9. The preparation method according to claim 7 or 8, characterized in that: The process parameters of the 3D inkjet printing include: surface air path pressure of 0.2-5 psi, voltage signal frequency of 20-100 Hz, pulse time of 0.3-0.5 ms, nozzle aperture of 50-100 μm, printing line speed of 8-20 mm / s, and printing line spacing of 0.2-0.5 mm.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The cold isostatic pressing pressure is 180-250 MPa, and the time is 0.5-2 h; The debonding environment is air, the temperature is 600-1000°C, and the time is 1-3h; The sintering is carried out under vacuum, and the pressure is controlled to be ≤10 -2 Pa, temperature is 1640-1750℃, time is 8-15h; The hot isostatic pressing atmosphere is argon, the pressure is 160-250 MPa, the temperature is 1600-1700°C, and the time is 3-6 hours; The annealing atmosphere is air or oxygen, the temperature is 1250-1350° C., and the time is 10-20 hours.
11. A YAG / Yb:YAG / YAG composite laser transparent ceramic obtained by the preparation method according to any one of claims 7 to 10, characterized in that: In the YAG / Yb:YAG / YAG composite laser transparent ceramic, both the YAG and Yb:YAG components are of cubic phase isotropic structure, the average grain size is 2-10 μm, the relative density is ≥99.9%, and the thickness of the Yb:YAG layer is 50-250 μm; When the thickness of the YAG / Yb:YAG / YAG composite laser transparent ceramic sample is 4.5-5.5 mm, the linear transmittance at a wavelength of 1030 nm is ≥80%.
Citation Information
Patent Citations
Method of YAG composite transparent laser ceramic
CN103058633A
ZrO2-toughened bioactive ceramic powder material for 3D printing and preparation and application thereof
CN105330285A
3D printing molding method for desktop-level ceramic product
CN107030853A
Preparation method of zirconia ceramic material extrusion type 3D printing material
CN113372114A
Preparation method of composite structure fluorescent ceramic based on 3D printing
CN116177995A